2021
DOI: 10.1111/ahe.12721
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific differences of the avian oesophagus: Histological and Ultrastructural study

Abstract: The oesophagus is a muscular tube comprised of cervical and thoracic regions. Several studies have clarified the histological structure of the oesophagus. However, its histoarchitecture in relation to variable dietary habits of each species is still unclear. In the current study, 21 pigeons, cattle egrets and ducks, n = 7, each was used. Macroscopically, the oesophagus of cattle egrets either the cervical or thoracic parts was the longest among the pigeons and ducks. Histologically, the oesophagus comprised of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…According to some authors, the structure of esophageal surface epithelium in birds depends on the type of dietary specialization. Therefore, it can be non-keratinized, partially keratinized, or keratinized (Ibrahim, 1992;Kharchenko & Byrka, 2003;El-naseery et al, 2021).…”
Section: Micromorphology Of the Esophagusmentioning
confidence: 99%
“…According to some authors, the structure of esophageal surface epithelium in birds depends on the type of dietary specialization. Therefore, it can be non-keratinized, partially keratinized, or keratinized (Ibrahim, 1992;Kharchenko & Byrka, 2003;El-naseery et al, 2021).…”
Section: Micromorphology Of the Esophagusmentioning
confidence: 99%
“…These results suggested that the dramatic morphological changes observed in crop sections corresponded to extreme transcriptomic reprogramming (Fig 2A and 2B) that reflected marked differences in female crop function among different breeding stages. It is important to note that the composition of crop cells undergoes significant change during breeding stages [15][16][17][18][19][20]. However, our bulk RNA-seq analyses only provide the average values of cell mixtures, thereby concealing cellular heterogeneity.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Crop mucosa consist of stratified squamous epithelial cells, including basal layer (undifferentiated cells, at the innermost of mucosa), a spinous layer (postmitotic cells), a granular layer (harboring flat cell), and a keratin layer (keratinized cells, at the surface of mucosa, which sloughs off to form pigeon 'milk') [3,6,[15][16][17][18][19][20]…”
Section: Spatially Resolved Transcriptomics In the Crop Of 'Lactating...mentioning
confidence: 99%